2019
DOI: 10.1089/tmj.2018.0236
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Methods for Designing and Developing Health Information Communication Technologies: A Systematic Review

Abstract: Background: Chronic disease management and maintaining healthy behaviors to prevent disease are important lifelong considerations. Adherence to prescribed management and behaviors often falls short of physician recommendations, which can result in negative health outcomes. Information communication technologies (ICTs) offer an approach to combat this issue. However, uptake and sustainability of ICTs have mixed results. One reason could be that technologies are often created without an understanding of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 99 publications
(332 reference statements)
0
7
0
2
Order By: Relevance
“…Therefore, adding new and more complex tasks and challenging content to the serious game prototype may help improve the longevity of play and make the game meaningful and helpful for children who have been diagnosed for a longer time and have already been taught the basics of carbohydrates [ 73 ]. In addition, the ability to tailor and customize information has been shown to make serious games more relevant to the user and increase their use [ 74 ]. DeSmet et al [ 75 ] reported that games are best tailored to both sociodemographic information (eg, age and gender) and behavioral change needs (eg, knowledge and motivation).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adding new and more complex tasks and challenging content to the serious game prototype may help improve the longevity of play and make the game meaningful and helpful for children who have been diagnosed for a longer time and have already been taught the basics of carbohydrates [ 73 ]. In addition, the ability to tailor and customize information has been shown to make serious games more relevant to the user and increase their use [ 74 ]. DeSmet et al [ 75 ] reported that games are best tailored to both sociodemographic information (eg, age and gender) and behavioral change needs (eg, knowledge and motivation).…”
Section: Discussionmentioning
confidence: 99%
“…Patient-centered design is one of the most common principles in digital health-related product development. 27 , 28 In pediatric health care studies, the patient-centered approach is recognized as a “family-centered design” as parents play a very important role in children's health care and promotion. In this study, the patient-centered design was implemented and informed by the target user interviews, including interviews with parents and investigation of the symptom experiences of children with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no overall significant effect on the HbA 1c levels, the results of our study demonstrate that those who used the app more had more improvements in their HbA 1c levels. This indicates the importance of creating an engaging intervention that is tailored to individual families in order to encourage long-term engagement [ 34 ]. Moreover, improvements in diabetes behavior and quality of life through long-term use of the MyT1DHero app intervention could also positively affect clinical diabetes outcomes; however, further research is needed.…”
Section: Discussionmentioning
confidence: 99%